Kebijakan Pengelolaan Pasar Rakyat dan Fungsi Sosial-Ekonomi Kawasan Perkotaan di Sengkang, Kabupaten Wajo - Sitti Rabiatul Wahdaniyah Herman (Prodi PWK Universitas Tadulako, 2026)
This study aims to examine the relationship between public market management policy and the socio-economic function of the urban area in Sengkang, Wajo Regency. The study employs a qualitative approach through a policy study based on the examination of legal instruments, regional planning documents, government administration reports, and official statistical data related to market management and urban dynamics. The findings show that the public market management policy in Wajo Regency has positioned the market as an important node of trade activities and public services within the urban structure of Sengkang. The policy also encompasses the dimensions of protection, empowerment, guidance, and market revitalization. However, at the implementation level, the linkage between market policy and the strengthening of the area’s socio-economic function has not yet operated optimally. The main constraints lie in the still limited integration with spatial planning, the management of supporting facilities, and the measurement of market service performance. This study underscores the need to strengthen the synchronization between public market policy and urban area planning so that the market functions not only as a space for transactions, but also as a driver of local economic growth and urban social services.